2011
DOI: 10.1111/j.1939-1676.2011.0695.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in North American Dogs from 1984 to 2004: An Investigation into Age‐, Size‐, and Breed‐Related Causes of Death

Abstract: Background: Anecdotal beliefs and limited research suggest variable patterns of mortality in age, size, and breed cohorts of dogs. Detailed knowledge of mortality patterns would facilitate development of tailored health-maintenance practices and contribute to the understanding of the genetic basis of disease.Hypothesis/Objectives: To describe breed-specific causes of death in all instances of canine mortality recorded in the Veterinary Medical Database (VMDB) a between 1984 and 2004. We hypothesized that cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
358
2
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 335 publications
(395 citation statements)
references
References 17 publications
23
358
2
12
Order By: Relevance
“…While large differences were seen in proportions of respiratory, gastrointestinal, and urogenital causes of death between humans and dogs, the proportion of neoplastic deaths is nearly identical between the two species (25.3% in humans; 27.4% in dogs; Figure 2c), although cancer risk is generally greater in large‐breed than small‐breed dogs (Fleming et al., 2011). Despite the similarity in risk of death due to neoplasia among humans and canines, the types of cancer seen in each species are only marginally correlated (Spearman rank ρ = 0.661, df  = 7, p  = .053).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While large differences were seen in proportions of respiratory, gastrointestinal, and urogenital causes of death between humans and dogs, the proportion of neoplastic deaths is nearly identical between the two species (25.3% in humans; 27.4% in dogs; Figure 2c), although cancer risk is generally greater in large‐breed than small‐breed dogs (Fleming et al., 2011). Despite the similarity in risk of death due to neoplasia among humans and canines, the types of cancer seen in each species are only marginally correlated (Spearman rank ρ = 0.661, df  = 7, p  = .053).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, our canine analysis makes the assumption that all dogs are drawn from the same pool and does not look at the effects of breed and size variation. Previous research has shown that even within a size class, breeds can differ in their multimorbidity (Jin et al., 2016) and mortality patterns (Fleming et al., 2011). Taken together, these limitations point to the need for more detailed data from canines representing the full diversity of ages, breeds, comorbidities, and environments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations